PENGARUH PEMBELAJARAN DARING TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS VIII DI SMP NEGERI 1 TOMA TAHUN PEMBELALAJARAN 2020/2021 - Lilis Sarika Bowo Laia (Kohesi : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Online learning is a learning system that is carried out in a network that is connected through a computer network, the internet which is done not face to face but visually, which can help the teaching and learning process that is carried out even though it is far away. Online learning has an effect on student achievement. Learning achievement that is focused on in this study is student achievement in Indonesian subjects. This study aims to determine the effect of online learning on student achievement in Indonesian class VIII subjects at SMP Negeri 1 Toma for the 2020/2021 academic year. The type of research used in this research is quantitative research with descriptive statistical methods. The population in this study were all class VIII students of SMP Negeri 1 Toma for the 2020/2021 academic year, because considering the large population, the researchers drew a research sample of 62 people using a sampling technique, namely simple random sampling. The instrument in this study used questionnaires, interviews and documentation in the form of a list of grades (reports) for odd semesters. The data analysis technique uses data description, coefficient of determination, and hypothesis testing. The test results in this study indicate that there is a significant influence between online learning on student achievement in Indonesian subjects, where taitung is 1.983> [tabet 1.67065. This means that Ho is rejected and Ha is accepted, meaning that there is an influence between online learning on student achievement in Indonesian subjects. From the results of this study, researchers suggest that students should be able to learn independently, so that online learning will make it easier for students to achieve good learning achievements.